Deep brain stimulation for phantom limb pain. (July 2022) - Pang, David; Ashkan, Keyoumars
Abstract: Phantom limb pain is a rare cause of chronic pain in children but it is associated with extremely refractory pain and disability. The reason for limb amputation is often due to treatment for cancer or trauma and it has a lower incidence compared to adults. The mechanism of why phantom pain exists remains uncertain and may be a result of cortical reorganisation as well as ectopic peripheral input. Treatment is aimed at reducing both symptoms as well as managing pain related disability and functional restoration. Neuromodulatory approaches using deep brain stimulation for phantom limb pain is reserved for only the most refractory cases. The targets for brain stimulation include the thalamic nuclei and motor cortex. Novel targets such as the anterior cingulate cortex remain experimental as cases of serious adverse effects such as seziures have limited their widespread uptake. A multidisciplinary approach is crucial to successful rehabilitation using a biopsychosocial pain management approach. Highlights: Pediatric phantom limb pain is seen less than in adult amputees but prevalence is variable. Phantom limb pain is likely to include both central cortical and peripheral mechanisms at the dorsal root ganglion. Deep Brain Stimulation as a treatment for phantom limb pain is based on adult and not pediatric evidence. Advances in non-invasive and closed loop stimulation has the potential to improve accessibility and outcomes.